2013
DOI: 10.1021/ja405891n
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of a Chromium(III)-Superoxo Complex and Nitric Oxide That Lead to the Formation of Chromium(IV)-Oxo and Chromium(III)-Nitrito Complexes

Abstract: The reaction of an end-on Cr(III)-superoxo complex bearing a 14-membered tetraazamacrocyclic TMC ligand, [CrIII(14-TMC)(O2)(Cl)]+, with nitric oxide (NO) resulted in the generation of a stable Cr(IV)-oxo species, [CrIV(14-TMC)(O)(Cl)]+, via the formation of a Cr(III)-peroxynitrite intermediate and homolytic O-O bond cleavage of the peroxynitrite ligand. Evidence for the latter comes from EPR spectroscopy, computational chemistry, and the observation of phenol nitration chemistry. The Cr(IV)-oxo complex does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…This seems to also correspond to known aqueous chemistry: peroxynitrite decomposes through various pathways, 3c,21 , including its degradation according to 2 − OON═O → O 2 + 2NO 2 − under basic conditions and relatively high concentration,s 21b,d,e and such reactivity has even been observed in aqueous chemistry with copper ion. 22 Similarly, Nam and co-workers reported formation of macrocyclic ligand-bound metal−PN complexes, for example, LCr III −PN 23 and non-heme-Fe III −PN 24 species, generated from precursor M−O 2 adducts reacting with NO (g) (Scheme 1). A novel case involves reaction of a macrocyclic ligand (L)Co–nitrosyl complex with potassium superoxide (KO 2 ), leading to LCo III −nitrite + ½ O 2(g) products, all proceeding through putative Co–PN intermediates (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This seems to also correspond to known aqueous chemistry: peroxynitrite decomposes through various pathways, 3c,21 , including its degradation according to 2 − OON═O → O 2 + 2NO 2 − under basic conditions and relatively high concentration,s 21b,d,e and such reactivity has even been observed in aqueous chemistry with copper ion. 22 Similarly, Nam and co-workers reported formation of macrocyclic ligand-bound metal−PN complexes, for example, LCr III −PN 23 and non-heme-Fe III −PN 24 species, generated from precursor M−O 2 adducts reacting with NO (g) (Scheme 1). A novel case involves reaction of a macrocyclic ligand (L)Co–nitrosyl complex with potassium superoxide (KO 2 ), leading to LCo III −nitrite + ½ O 2(g) products, all proceeding through putative Co–PN intermediates (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In such biomimetic studies, mononuclear metal-superoxo species have been shown to react with NO to produce metal-PN (M n+ – − OON=O) intermediates, including examples with heme, non-heme Fe, Co or Cu. 12 For example, we reported recently the conversion of a non-heme Cr IV -peroxo complex to a Cr III -nitrate ion upon addition of NO, 13a whereas the reaction of a Cr III -superoxo complex with NO gave a high-valent Cr IV -oxo species and nitrogen dioxide (NO 2 ) via the formation of a presumed Cr III -PN intermediate. 13b Thus, a variety of outcomes can occur when metal complexes in varying oxidation states mediate reactions of NO (or NO + ) with differing reduced O 2 -derivatives (e.g., superoxide or peroxide).…”
mentioning
confidence: 99%
“…12 For example, we reported recently the conversion of a non-heme Cr IV -peroxo complex to a Cr III -nitrate ion upon addition of NO, 13a whereas the reaction of a Cr III -superoxo complex with NO gave a high-valent Cr IV -oxo species and nitrogen dioxide (NO 2 ) via the formation of a presumed Cr III -PN intermediate. 13b Thus, a variety of outcomes can occur when metal complexes in varying oxidation states mediate reactions of NO (or NO + ) with differing reduced O 2 -derivatives (e.g., superoxide or peroxide). Included is the capture of a peroxynitrite (or NO 2 ) intermediate via nitration of added phenols, which is analogous to biologically well established tyrosine nitration which effects biomolecule damage or participates in cellular signalling events.…”
mentioning
confidence: 99%
“…4,5 In biomimetic studies, mononuclear metal-O 2 complexes, best described as metal-superoxo species, are reported to react with NO to give metal-peroxynitrite (M n + –OON=O, PN) 4,6 intermediates. 79 To mimic NOD reactivity, we recently reported the conversion of NO and metal-O 2 species to NO 3 − and metal-oxo species, respectively, using peroxide or superoxide complexes of chromium-TMC (TMC = N -tetramethylated cyclam); a Cr(IV)-peroxo complex ([Cr IV- (12-TMC)(O 2 )(Cl)] + ) reacted with NO to form a Cr(III)-nitrato complex ([Cr III (12-TMC)(NO 3 )(Cl)] + )), 10 whereas a Cr(III)-superoxo complex ([Cr III (14-TMC)(O 2 )(Cl)] + ) and NO gave a Cr(IV)-oxo complex ([Cr IV- (14-TMC)(O)(Cl)] + ) and NO 2 via the formation of a presumed Cr(III)-peroxynitrite intermediate ([Cr III (14-TMC)(OON=O)(Cl)] + ) ‡ 11. …”
mentioning
confidence: 99%